Menyimak Figurrabbi Dalam Judaisme Dan Relevansinya Bagi Formasi Guru Agama Milenial - Yosef Masan Toron (Jurnal Alternatif Wacana Ilmiah Interkultural, 2019)
Rabbi among the Jews was the very important group. They had the most strategic and central roles among the Jewish community, not only in the religious field, but also in differents fields of life. Shmuel Kogan, a Jewsih Scholar, responding the question about the Rabbi, testified clearly that “rabbi was the servant of community ”. The Rabbis in the past offered their whole life to teach the Torah, the most fundamental law among the Jews. Based on the Torah, all the Jews in the past were able to struggle in responding different challanges and difficulties. Based on this experience, we could say that the Bible, the word of God written by human being and inspired by the High Being can be used as the inspiration to build a sustainable community. Reflecting on our millennial communities, especially among the Christian youth, we find out that most of our chiristians millennial youth are less interested to the religion. The word of God, written in the Bible is only a kind of strange stories that has no relationship to their millennial experiences and needs. Facing a such challenging condition, the experience of the rabbis in the past could be a good model and example for the teachers who are responsible to teach the Religion and the Bible to the millennial christen student. Using the experiences of the Rabbis among the Jews in the past, the teachers of religion can develop a best way of teaching religion for the millenials christian.